The Effect of Problem Based Learning Models and Analysis Skills on Mathematics Learning Outcomes in Primary Schools - Sulastri, Dinia; Halqi, Muhammad; Marhamah, Marhamah (Sumber Belajar Sejahtera, 2024)
This research aims to determine the effect of the problem based learning model and analytical skills on elementary school students' mathematics learning outcomes. This type of research is quantitative research using experimental methods with a research design using a 2x2 factorial design. The research was carried out at SDN 3 Lenek Daya. Data collection techniques use tests to determine learning outcomes and students' level of analysis. The results of the research show that 1) there is a difference in the mathematics learning outcomes of students who are taught using the Problem Based Learning (PBL) and the learning outcomes of students who use the Cooperative Think-Pair-Share (TPS) model, indicated by the difference in Fhitung values ​​greater than Ftable by (17,991 > 3.44). 2) there is an interaction effect between the PBL and analytical skills on students' mathematics learning outcomes, as evidenced by the Fhitung value being greater than Ftable (4.549 > 3.44) with a Sig value < α value (0.029 < 0.05). 3) there are differences in mathematics learning outcomes for students who have a high analysis of learning using PBL and TPS, this is because Fhitung is greater than Ftable (6.472 > 3.44), as well as the sig value < α value (0.030 < 0.05). 4) there are differences in mathematics learning outcomes for students who have low analytical skills who are taught using the PBL and TPS models, because the Fhitung value is greater than Ftable (19,950 > 3.44) while the sig value < α value (0.001 < 0.05)